Philosophy and Society: Rethinking Moral Responsibility in a Globalized World - Godlif Sianipar; Shari Lee; Raymond Foster (Yayasan Adra Karima Hubbi, 2026)
Background. In the age of globalization, the concept of moral responsibility has become increasingly complex, as individuals, communities, and nations are interconnected in ways that transcend traditional boundaries. The global nature of economic, environmental, and social issues has raised important questions about the extent of individual and collective responsibility in addressing these challenges. Classical philosophical theories on morality, responsibility, and ethics offer valuable insights, but they must be reconsidered in light of contemporary global dynamics. Purpose. The objective of this research is to explore the evolving concept of moral responsibility in a globalized world, focusing on how traditional moral frameworks can be rethought to address the ethical challenges posed by globalization. The study seeks to bridge the gap between classical moral philosophy and contemporary global issues, offering a new perspective on individual and collective moral duties. Method. This research employs a qualitative, conceptual analysis of moral responsibility, drawing from classical philosophical theories and contemporary global issues. It includes a literature review and critical examination of key ethical frameworks to assess their relevance in today’s interconnected world. Results. The study finds that while classical moral theories still offer valuable insights, they need to be expanded to account for the interconnectedness of global societies, the complexity of modern challenges, and the roles of individuals and institutions in addressing these issues. Conclusion. The research concludes that moral responsibility in a globalized world requires a rethinking of traditional ethical frameworks, incorporating both individual and collective duties in addressing global challenges.